Challenges in recruiting international students of Netasia Education Centre / Nur Aina Shafiei - Shafiei, Nur Aina (2009)
Malaysian government has set the target to become Education Hub in 2010 with 100,000 international students’ study in Malaysia. To support the government target, many recruitment agencies was established. The main area of this study is the challenges that the recruitment agency has to facing in order to recruit international students. The methods used to complete this study are through the company web site, information from the staff, observation and interview also make some additional from the text book and journal. Recruiting international students are quite interesting and challenging. This is because the organization has to deal with the students that have difference background and language. The organization has to strive in order to maintain its existing in this industry. Besides, the management is not well organized and monitor makes the organization in unstable condition. Despite, organization also should aware with the problems arose and taken several actions to solve the problems before it gives more trouble to the organization. Results found from the study show that the organization have to restructure the organization to brand new one to be competitive enough to strive in this business industry. Organization has to concern about the strategies and plans to sustain the demand and supply of customers to meet the objectives. The issues that come out try to handle it prior might affect the organization image and reputation. Many factors should be considered and actions taken to ensure that the organization could well manage and operate. This is to ensure that the customers will satisfy with the services offer by organization.